The relationship between positive future thinking, entrapment, defeat and death-related mental imagery in individuals with and without a suicidal history: an experimental study - Köse, Gonca; Evans, Jonathan J.; O’Connor, Rory C. (Frontiers in Psychology, 2025)
BackgroundAlthough there is growing evidence that impaired positive future thinking is associated with suicide risk, the relationship between positive future thinking and suicidal thoughts or suicidal behaviours has yet to be completely understood. Therefore, this experimental study explored the role of positive future thinking in those with different suicidal histories.MethodsFifty-three adults were recruited to a study, which included completing a range of self-reported measures (suicidal history, suicide ideation, defeat, entrapment, depression, and death-related mental imagery) and experimental tasks (verbal fluency or cognitive performance task, positive future thinking task and positive-and negative-mood induction). The study compared 30 individuals who had a history of suicidal thoughts/behaviours and 23 with no suicidal history in terms of positive future thinking before and after a negative mood induction and on established psychological markers of suicide risk (e.g., depression, defeat, entrapment, and death-related mental imagery).ResultsParticipants with a history of suicidal thoughts/behaviours reported significantly fewer positive future thoughts (PFT) than participants without past suicidal thoughts/behaviours. Mean scores for PFT from pre-to post-negative mood induction decreased significantly in the participants with a history of suicidal thoughts/behaviours but not in those without a suicidal history. Individuals with a history of suicidal thoughts/behaviours reported significantly higher levels of death-related mental imagery, depression, entrapment, and defeat compared to those without past suicidal thoughts/behaviours.ConclusionThis study provides experimental evidence that positive future thinking is implicated in the suicidal process. In addition, positive future thinking is affected by a negative mood induction, especially in individuals with a suicidal history. Changes in positive future thinking could be usefully assessed in clinical contexts.